Specificity and control of uptake of purines and other compounds in Bacillus subtilis. - Beaman, T C (1983)
Certain nucleotides control adaptation to changing nutrition or differentiation (sporulation) resulting from a general nutritional deficiency. To maintain the adaptation or differentiation process, once it has started, it may have been important for cells to evolve several independent and metabolically controllable systems enabling the uptake and metabolism of various nucleic acid bases or nucleosides. We have analyzed the cellular reactions with these compounds by measuring both their effect on growth and their uptake in appropriately chosen auxotrophic and uptake mutants. We have found one uptake system for guanine and hypoxanthine, another one for guanosine and inosine, and three other systems for adenine, adenosine, and uracil. The uptake systems of guanine-hypoxanthine and guanosine-inosine are inhibited by the stringent response to amino acid deprivation (increase of guanosine 5'-diphosphate-3'-diphosphate), but they do not depend on the concentration of GTP, which decreases during sporulation. In contrast, the uptake of Ura depends on the presence of GTP, regardless of whether a GTP decrease was produced by the stringent response or otherwise. This was the only uptake system whose decrease was always correlated with the onset of sporulation. The uptake of other compounds, e.g., alpha-methylglucoside and alpha-aminoisobutyric acid, decreased under some, but not all, sporulation conditions.